Bone health in the prostate cancer patient receiving androgen deprivation therapy: a review of present and future management options - Egerdie, Blair; Saad, Fred (Canadian Urological Association Journal, 2013)
Osteoporosis and bone fractures are frequently overlooked complications of androgen deprivation therapy in men with nonmetastatic prostate cancer. All such patients should have their bone mineral density (BMD) monitored and be offered preventive measures, such as calcium and vitamin D supplementation; patients with low BMD should be offered treatment. Several agents, including bisphosphonates, are available (although this use is currently offlabel), and upcoming treatments, such as denosumab and toremifene, have shown promise in reducing fracture risk in these patients. L’ostéoporose et les fractures osseuses sont des complications souvent négligées du traitement antiandrogénique chez les hommes atteints d’un cancer de la prostate non métastatique. La teneur minérale des os de ces patients devrait être surveillée, et des mesures préventives, comme la prise de suppléments de calcium et de vita - mine D, devraient être offertes. Les patients présentant une faible teneur minérale des os devraient se voir offrir un traitement approprié. Plusieurs agents, y compris des bisphosphonates, sont offerts sur le marché (quoique cette indication ne soit pas officiellement approuvée à l’heure actuelle), et des traitements en cours d’étude, comme le dénosumab et le torémifène, se sont révélés prometteurs dans la réduction du risque de fracture chez ces patients.